MANAGEMENT OF OPEN TIBIAL FRACTURES AT AYUB TEACHING HOSPITAL, ABBOTTABAD - Sultan, Shahid; Shah, Ali Asghar (Journal of Ayub Medical College Abbottabad, 2001)
Background: Open fractures of tibia are usually caused by high-energy injury. Management of such injuries requires care of contaminated soft tissue injury involving skin, muscles and neurovascular structures. Treatment of fracture, which is badly comminuted and potentially contaminated, is always a problem. While limb salvage is the initial aim. medium and long-term problems with soft tissue cover, infection and union are all too common and result in serious disability. Methods: 32 open grade-111 tibial fractures were treated with AO (Arbeitsgemeinschaft fur Osteosynthesefragen) tubular external fixator. The management and outcome were reviewed and tabulated. Results: One out of 32 required primary amputation due to delayed vascular repair. The remainder received standardized wound care consisting of surgical debridement and delayed closure of wound. Once the soft tissue envelope healed and fracture was sticky external frame was removed and patella tendon bearing cast applied. In selected cases internal Fixation was done (n=8, in 5 intramedullary nailing and in 3 plating). Nineteen cases were treated in PTB cast and 4 cases in external fixation till union. Deep infection rate was 13% and pin tract infection 10%. In 31 cases union was achieved in 32 weeks (24 weeks to 62 weeks).